Uniformity under in vitro conditions: Changes in the phenotype of cancer cell lines derived from different medulloblastoma subgroups - Chlapek, Petr; Zitterbart, Karel; Kren, Leos; Filipova, Lenka; Sterba, Jaroslav; Veselska, Renata (PloS one, 2017)
Medulloblastoma comprises four main subgroups (WNT, SHH, Group 3 and Group 4) originally defined by transcriptional profiling. In primary medulloblastoma tissues, these groups are thought to be distinguishable using the immunohistochemical detection of β-catenin, filamin A, GAB1 and YAP1 protein markers. To investigate the utility of these markers for in vitro studies using medulloblastoma cell lines, immunoblotting and indirect immunofluorescence were employed for the detection of β-catenin, filamin A, GAB1 and YAP1 in both DAOY and D283 Med reference cell lines and the panel of six medulloblastoma cell lines derived in our laboratory from the primary tumor tissues of known molecular subgroups. Immunohistochemical detection of these markers was performed on formalin-fixed paraffin-embedded tissue of the matching primary tumors. The results revealed substantial divergences between the primary tumor tissues and matching cell lines in the immunoreactivity pattern of medulloblastoma-subgroup-specific protein markers. Regardless of the molecular subgroup of the primary tumor, all six patient-derived medulloblastoma cell lines exhibited a uniform phenotype: immunofluorescence showed the nuclear localization of YAP1, accompanied by strong cytoplasmic positivity for β-catenin and filamin A, as well as weak positivity for GAB1. The same immunoreactivity pattern was also found in both DAOY and D283 Med reference medulloblastoma cell lines. Therefore, we can conclude that various medulloblastoma cell lines tend to exhibit the same characteristics of protein marker expression under standard in vitro conditions. Such a finding emphasizes the importance of the analyses of primary tumors in clinically oriented medulloblastoma research and the urgent need to develop in vitro models of improved clinical relevance, such as 3D cultures and organotypic slice cultures.
Keywords: Cerebellum; mozeček; kojenec; mladiství; imunohistochemie; imunoblotting; mužské pohlaví; Infant; Adult; mladý dospělý; Tumor Cells, Cultured; dítě; Biomarkers, Tumor; Child; Medulloblastoma; Child, Preschool; Immunohistochemistry; meduloblastom; Immunoblotting; Young Adult; ženské pohlaví; nádorové biomarkery; Humans; předškolní dítě; fluorescenční protilátková technika; nádory mozečku; Fluorescent Antibody Technique; dospělí; Cerebellar Neoplasms; Female; nádorové buňky kultivované; Adolescent; lidé; Male